The Factors Influencing the People of Aceh Tamiang in Dressing by Islamic Dress Code - Fahriansah Fahriansah; Khairatun Hisan; Fachrizal Fachrizal; Zubir Zubir (Proceedings of AICS - Social Sciences, 2018)
This paper aims to find out the factors influencing the people of Aceh Tamiang in wearing Islamic dress properly and effectively as stated in Article 13 of Qanun No. 11 of 2002. Using purposive sampling method, the subjects of this study were determined to be 75 people consisting of 15 (fifteen) teachers/lecturers, 15 (fifteen) office workers, 15 (fifteen) merchants, and 30 (thirty) university students. The data gathered via interview, observation, and questionnaire was analysed through qualitative approach. The result shows that the factors influencing perception formation of people of Aceh Tamiang towards Islamic dress in Article 13 of Qanun No. 11 of 2002 consist of external and internal ones. The external factors are: (1) the lack of information received by people about the criteria of Islamic dress in Article 13 of Qanun No. 11 of 2002, (2) the limited script of Article 13 of Qanun No. 11 of 2002 received by the people, and (3) the less appropriate and effective socialising system done by the government of Aceh, and the small number of the people who admittedly have ever read the content of Article 13 of Qanun No. 11 of 2002. The internal factors are: (1) the people’s lack of understanding towards Islamic dress stated in Article 13 of Qanun No. 11 of 2002, (2) the presumption that Arabic culture (Arabism) as Islamic teachings particularly in dress code, and (3) the desire to show up-to-date fashion style while not deserting Islamic dress code. Therefore, there is unity between Islamic values and local culture with globalisation/foreign culture.Keywords: internal factors, external factors, Islamic dress code, article 13 of Qanun No 11 of 2002.